Pemahaman Physical Literasi Guru TK dalam Aktivitas Motorik Anak - Juniarti, Yenti; Puspa Ardini, Pupung; Ramadan, Gilang; Puji Lestari, Dwi (Jurnal Pelita PAUD, 2024)
Abstract: This study aims to understand preschool teachers' understanding of physical literacy in implementing children's motor activities. Physical literacy is an important concept in the physical development of young children, encompassing basic physical skills and the ability to move confidently and competently. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with several preschool teachers and observations of motor activities conducted in the classroom. The findings show that most preschool teachers have a basic understanding of physical literacy, although the level of understanding and its implementation in children's motor activities varies. Some teachers have successfully designed and carried out activities that optimally support children's motor development, while others require further knowledge enhancement and training regarding this concept. Factors influencing this understanding include educational background, teaching experience, and school support. The study concludes that enhancing the understanding of physical literacy among preschool teachers is crucial for creating an environment that fully supports children's physical development. It is hoped that the findings will contribute to the development of early childhood education curricula, particularly in relation to motor learning. Keywords: Understanding, Physical Literacy, Preschool Teachers, Motor Activities, Early Childhood Education, Qualitative Research.